Laminaria japonica fucoidan ameliorates cyclophosphamide‐induced liver and kidney injury possibly by regulating Nrf2/HO‐1 and TLR4/NF‐κB signaling pathways. (3rd November 2021) - Tian, Shanshan; Jiang, Xiaoxia; Tang, Yunping; Han, Tao
Abstract: BACKGROUND: During clinical practice, cyclophosphamide (CTX) can lead to liver and kidney injury in vivo . In this study, we established a liver and kidney injury model by injecting CTX (80 mg kg −1 d −1 ) into male ICR mice, and then mice were treated with saline and fucoidan (20 or 40 mg kg −1 ), respectively. Subsequently, the liver and kidney toxicity indices, the expression levels of malonic dialdehyde (MDA), inflammatory factors, and the main protein levels of the Nrf2/HO‐1 and TLR4/NF‐κB pathways were determined. RESULTS: Our results indicated that fucoidan could significantly decrease serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatinine (CRE), and urea (BUN) in the test group compared to the model group. Fucoidan administration caused reductions in MDA, interleukin‐6 (IL‐6), IL‐1β, and tumor necrosis factor alpha (TNF‐α) levels and improved superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px), and catalase (CAT) activities in the liver and kidney of CTX‐induced mice. Fucoidan up‐regulated the Nrf2/HO‐1 pathway and enhanced the protein levels of Nrf2, HO‐1, GCLM, and NQO1. Moreover, fucoidan down‐regulated the TLR4/NF‐κB pathway, as indicated by decreased levels of TLR4, NF‐κB p65, NF‐κB p50, and increased IκBα level in liver and kidney tissues. CONCLUSION: Our studies suggest that fucoidan can ameliorate CTX‐induced liver and kidney injury, potentially via up‐regulating the Nrf2/HO‐1 pathway and inhibiting the TLR4/NF‐κB pathway. © 2021 Society of Chemical Industry.